Child Identity Card (Kia) Policy Implementation In The Population And Civil Registration Office Kuantan Singingi Regency - Syaprianto, Syaprianto; Maryati , Yogi Oktaris Maryati (UIR Press, 2023)
This study aims to determine the Implementation of the Child Identity Card (KIA) Policy at the Population and Civil Registration Office of Kuantan Singing Regency and to find out the inhibiting factors for the implementation of the Child Identity Card program by the Population and Civil Registration Office of Kuantan Singing Regency. The research method used in this research is qualitative, data collection using interview techniques, observation, and documentation. The results of this study indicate that the Implementation of the Child Identity Card (KIA) Policy at the Population and Civil Registration Office of Kuantan Singing Regency has been carried out but has yet to be maximally implemented. This can be seen from the number of human resources in Policy Implementation, which still needs to be considered. Besides that, public awareness to take care of the KIA Child Identity Card (KIA) is still low. So the researcher's suggestion to the Population and Civil Registration Office of Kuantan Singing Regency is expected to be able to increase the number of employees who specifically handle KIA so that services and socialization can be carried out optimally and need to increase the number of printing machines for the Child Identity Card (KIA).